National Heart Institute College (IJN College) visits Faculty of Pharmacy, UiTM / Zakiah Mohd Noordin - Mohd Noordin, Zakiah (Faculty of Pharmacy, 2024)
On June 14, 2024, the Faculty of Pharmacy, Universiti Teknologi MARA (UiTM), had the distinct honour of hosting delegates from the National Heart Institute College (IJN College). The visit took place at the Gallery, FF1 Block, Faculty of Pharmacy, and was attended by representatives from both institutions.